Establishing a hyperacute stroke service during the COVID-19 pandemic: our institutions one year experience - Abdul Rashid, Anna Misya’il; Md Noh, Mohamad Syafeeq Faeez; Yusof Khan, Abdul Hanif Khan; Loh, Wei Chao; Baharin, Janudin; Ibrahim, Azliza; Ishak, Fadhilah Hani; Sardi, Aminuddin; Hanapai, Ahmad Firdaus; Mohamad, Nur Afiqah; Inche Mat, Liyana Najwa; Hoo, Fan Kee; et al. (Springer Science and Business Media, 2023)
Background and aims: The corononavirus 2019 (COVID-19) pandemic resulted in modifications in the workflow and redistribution of human resources, causing challenges in setting up of an acute stroke service. We would like to share our preliminary outcome amid this pandemic, to determine if the implementation of COVID-19 standard operating procedures (SOPs) affected the delivery of our hyperacute stroke service. Methods: We retrospectively analyzed one-year data from our stroke registry that began with the establishment of our hyperacute stroke service at Universiti Putra Malaysia Teaching Hospital from April 2020 until May 2021. Results: Setting up acute stroke services during the pandemic with constrained manpower and implementation of COVID-19 SOPs, was challenging. There was a significant dip of stroke admission from April to June 2020 due to the Movement Control Order (MCO) implemented by the government to curb the spread of COVID-19. However, the numbers of stroke admission steadily rose approaching 2021, after the implementation of recovery MCO. We managed to treat 75 patients with hyperacute stroke interventions i.e. intravenous thrombolysis (IVT), mechanical thrombectomy (MT) or both. Despite implementing COVID-19 SOPs and using magnetic resonance imaging (MRI) as our first line acute stroke imaging modality, clinical outcomes in our cohort were encouraging; almost 40% of patients who underwent hyperacute stroke treatment had early neurological recovery (ENR), and only 33% of patients had early neurological stability (ENS). In addition, we were able to maintain our door-to-imaging (DTI) and door-to-needle (DTN) time in line with international recommendations. Conclusions: Our data reflects that COVID-19 SOPs did not deter successful delivery of hyperacute stroke services in our center. However, bigger and multi center studies are required to support our findings.